Marketing efficiency, pricing and policy implications: a case study of milk marketing in Addis Ababa, Ethiopia - Mbogoh, S.G. (International Livestock Centre for Africa, 1992)
This case study examines the marketing system for fresh liquid milk in Addis Ababa and its environs (i.e. the catchment area for fresh milk within a 130 km. radius of the city of Addis Ababa) from the retail end of the system to determine the relative efficiency of alternative marketing systems for dairy products. Aspects examined were (1) consumer price levels, (2) the types, reliability and stability or flexibility of the services offered to the consumers, (3) the responsiveness of alternative marketing systems to consumer demands and (4) the contribution of alternative marketing systems to the maintenance of achievement of some specified goals of marketing policies, such as product quality and hygiene standards.